Effect of staurosporine on cycle human gastric cancer cell - Ha, Min-Wen (World J Gastroenterol, 2004)
AIM: To study the effect of staurosporine (ST) on the cell cycle of human gastric cancer cell lines MGC803 and SGC7901. METHODS: Cell proliferation was evaluated by trypan blue dye exclusion method. Apoptotic morphology was observed under a transmission electron microscope. Changes of cell cycle and apoptotic peaks of cells were determined by flow cytometry. Expression of P21(WAF1) gene was examined using immunohistochemistry and RT-PCR. RESULTS: The growth of MGC803 and SGC7901 cells was inhibited by ST. The inhibitory concentrations against 50% cells (IC(50)) at 24 h and 48 h were 54 ng/ml and 23 ng/ml for MGC803, and 61 ng/ml and 37 ng/ml for SGC7901. Typical apoptotic bodies and apoptotic peaks were observed 24 h after cells were treated wth ST at a concentration of 200 ng/ml. The percentage of cells at G(0)/G(1) phase was decreased and that of cells at G(2)/M was increased significantly in the group treated wth ST at the concentrations of 40 ng/ml, 60 ng/ml, 100 ng/ml for 24 h, compared with the control group (P < 0.01). The expression levels of P21(WAF1) gene in both MGC803 and SGC7901 cells were markedly up-regulated after treatment with ST. CONCLUSION: ST can cause arrest of gastric cancer cells at G(2)/M phase, which may be one of the mechanisms that inhibit cell proliferation and cause apoptosis in these cells. Effect of ST on cells at G(2)/M phase may be attributed to the up-regulattion of P21(WAF1) gene.